'Really caring, really curious, and really there': a qualitative exploration of therapeutic presence from a Hakomi therapy perspective. Issue 2 (3rd April 2022) - Kelly, Scott William; Papps, Fiona Ann
ABSTRACT: Therapeutic presence (TP) is the ability to be fully human and fully engaged with another person emotionally, cognitively, physically, and spiritually, and underpins all efficacious interventions. Ron Kurtz's Hakomi method is a mindfulness based, psychodynamic psychotherapy that integrates the body into the therapeutic process, emphasising the personhood of the therapist as a therapeutic tool. The present research used a qualitative framework to explore Hakomi therapists' understanding of TP. Four graduates of the full professional Hakomi training were interviewed about their lived experiences of TP. Interpretative Phenomenological Analysis (IPA) applied to resultant verbatim transcripts showed that two elements comprised TP: felt state of being and dual awareness. Central to creating TP is a particular personhood of the therapist, in which Hakomi practitioners are explicitly and specifically trained. This unique Hakomi-based understanding of TP can support therapeutic change and could be incorporated into training of mental health practitioners, regardless of therapeutic modality.